+0  
 
-3
207
2
avatar+229 

y=x+5 

 

y=-2x-1

 

A (0, - 1)

 

B ( 0,5)

 

C  (- 2,3)

 

D ( -2 , -1 ) 

 Mar 8, 2019
 #1
avatar+19908 
0

y =  x+5 

Sub this value of y into the second equation:

 

x+5 = -2x-1   solve for x   ====> add  2x to each side

3x + 5 = -1    subtract  5 from each side

3x = -6

x = -2        NOW, sub this into one of the first two equations to find 'y'

 

y = x+5

y = -2 + 5  = 3

 Mar 8, 2019
 #2
avatar+106533 
+1

y = x + 5

y = -2x - 1

 

Set the y's equal

 

x + 5  = - 2x - 1        subtract x, add 1 from/to each sides

 

6 = - 3x              divide both sides by - 3

 

-2 = x

 

And using  y = x + 5

 

y = - 2 + 5

 

y = 3

 

(  -2, 3)  = (x , y)

 

 

cool cool cool

 Mar 8, 2019

23 Online Users